2004
DOI: 10.1161/01.cir.0000146334.96820.6e
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Ambulatory Heart Rate Variability

Abstract: Background-Reduced heart rate variability (HRV) is a prognostic factor for cardiac disease and cardiac mortality.Understanding the sources of individual differences in HRV may increase its diagnostic use and provide new angles for preventive therapy. To date, the contribution of genetic and environmental factors to the variance in HRV has not been investigated during prolonged periods of ambulatory monitoring in a naturalistic setting. Methods and Results-In 772 healthy twins and singleton siblings, ambulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 37 publications
5
70
1
3
Order By: Relevance
“…Some of the most important factors are shortly discussed in the following paragraphs. A significant genetic contribution to HRV has been established in laboratory twin and family studies (Kupper et al 2004;Singh et al 1999;Uusitalo et al 2007). A genetic contribution of 13-39 % of resting HRV has been reported, increasing up to 51 % during exposure to mentally and emotionally demanding tasks.…”
Section: Factors Affecting Hrvmentioning
confidence: 97%
See 1 more Smart Citation
“…Some of the most important factors are shortly discussed in the following paragraphs. A significant genetic contribution to HRV has been established in laboratory twin and family studies (Kupper et al 2004;Singh et al 1999;Uusitalo et al 2007). A genetic contribution of 13-39 % of resting HRV has been reported, increasing up to 51 % during exposure to mentally and emotionally demanding tasks.…”
Section: Factors Affecting Hrvmentioning
confidence: 97%
“…A genetic contribution of 13-39 % of resting HRV has been reported, increasing up to 51 % during exposure to mentally and emotionally demanding tasks. An ambulatory 24 h recording revealed that the mean genetic contribution of SDNN and RMSSD varied from 35 to 47 % and from 40 to 48%, respec-tively (Kupper et al 2004). Martinmäki et al (2006b) investigated the intraindividual variation of HRV indices to measure modulation of vagal activity and found a large variation in the quantitative relationship between vagal component (high frequency power, HFP) of HRV and vagal effects on the heart.…”
Section: Factors Affecting Hrvmentioning
confidence: 99%
“…Furthermore, every 30 min blood pressure was recorded using a Spacelabs 90207 ambulatory blood pressure monitor (Redmont, Washington, USA). Results on cardiovascular measures have been published elsewhere (Kupper et al, 2004(Kupper et al, , 2005. Subjects wore the VU-AMS monitor the entire day and night until after awakening the next morning.…”
Section: General Proceduresmentioning
confidence: 99%
“…Short-term HRV analysis used in the present study is a highly reproducible method (Tarkiainen et al 2005) and is of significant clinical relevance (Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology 1996; Pumprla et al 2002). Therefore, HRV can be used to search for genetic variation influencing autonomic modulation and various related diseases including cardiac disease (Kupper et al 2004). When each a 1 -AR or a 2 -AR subtype-selective agent in humans is available, our understanding of the physiological and clinical importance of the a-AR polymorphisms will be further refined.…”
Section: Discussionmentioning
confidence: 99%